Implementation of an urban efficiency index to comprehend post-metropolitan territories—The case of Greater Milan in Italy. (July 2019) - Caputo, Paola; Pasetti, Giulia; Ferrari, Simone
Highlights: A fuzzy logic model is proposed to understand urban dynamics and efficiency. A summary urban efficiency index is defined and calculated for 904 municipalities. Results are represented by clustering and GIS in a 100 km 2 territory around Milan. Results support decisions for urban renewal and environmental pressure reduction. Further improvements will be a more systematic structure of the model. Abstract: The objective of this research is to develop a large-scale interdisciplinary urban analysis of a post-metropolitan area in Northern Italy and provide outcomes that can be useful for policymakers, public utilities, urban designers, and other stakeholders in defining strategies to improve the territory. This research, implemented within a wide national academic study on several urban regions in Italy, focuses on a 100 × 100 km 2 square territory around the centre of Milan that encompasses 904 municipalities. The main local input and output flows are analysed for each municipality by considering available databases. Urban performance is investigated in the research framework of urban metabolism, by applying a fuzzy logic model. The overall structure of the model, definition of subsystems, set of indicators, adopted benchmarks, and levels of importance of variables are calibrated to suit the particular context of applications. The model provides the UEI (urban efficiency index) outcome and a geographical information system (GIS) representation to facilitate the comparison between municipalities and territories and determine the low or high-performance areas that necessitate further investigations. This work represents an important attempt in developing and applying methods for supporting decisions and defining policies towards more sustainable urban areas.